The Effect of Education, Poverty, and Population Growth on Economic Growth in South Sulawesi in 2010-2022 - Basri Bado; Irwandi; Yusri Karmila (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to analyze how the variables of education, poverty and population growth affect economic growth in South Sulawesi so that later it can be used as a basis for determining policies in increasing economic growth in South Sulawesi. While the analysis method used in this research is multiple linear regression analysis method. The results of data estimation using multiple regression analysis show that the education variable has a negative and insignificant effect on economic growth, the poverty variable has a significant effect on economic growth and population growth has a significant effect on economic growth in South Sulawesi. Education, poverty and population growth variables together have no effect on economic growth in South Sulawesi.